Safety and efficacy of COVID-19 vaccine immunization during pregnancy in 1024 pregnant women infected with the SARS-CoV-2 Omicron virus in Shanghai, China - Deng, Hongmei; Jin, Yinpeng; Sheng, Minmin; Liu, Min; Shen, Jie; Qian, Wei; Zou, Gang; Liao, Yixin; Liu, Tiefu; Ling, Yun; Fan, Xiaohong (Frontiers in Immunology, 2024)
Background Large sample of pregnant women vaccinated with COVID-19 vaccine has not been carried out in China. The objective of this study was to evaluate the safety and effectiveness of COVID-19 inactivated vaccine in pregnant women infected with the SARS-CoV-2 Omicron variant. Methods A total of 1,024 pregnant women and 120 newborns were enrolled in this study. 707 pregnant women received one to three doses of the inactivated COVID-19 vaccine, and 317 unvaccinated patients served as the control group. A comparison was made between their clinical and laboratory data at different stages of pregnancy. Results The incidence rate of patients infected with Omicron variant in the first, the second, and the third trimesters of pregnancy was 27.5%, 27.0%, and 45.5% in patients during, respectively. The corresponding length of hospital stay was 8.7 ± 3.3 days, 9.5 ± 3.3 days, and 11 ± 4.3 days, respectively. The hospitalization time of pregnant women who received 3 doses of vaccine was (8.8 ± 3.3) days, which was significantly shorter than that of non-vaccinated women (11.0 ± 3.9) days. (P<0.0001). The positive rate of SARS-CoV-2 IgG in patients in the early stage of pregnancy was 28.8%, while that in patients in the late stage of pregnancy was 10.3%. However, three-doses of vaccination significantly increased the SARS-CoV-2 IgG positive rate to 49.5%. The hospitalization time of SARS-CoV-2 IgG-positive patients was shorter than that of negative patients (9.9 ± 3.5 days), which was 7.4 ± 2.0 days. 12.2% of vaccinated women experienced mild adverse reactions, manifested as fatigue (10.6%) and loss of appetite (1.6%). The vaccination of mother did not affect her choice of future delivery mode and the Apgar score of their newborn. All newborns tested negative for SARS-CoV-2 nucleic acid, as well as for IgG and IgM antibodies. Conclusions Women in the third trimester of pregnancy are highly susceptible to infection with the Omicron strain. The vaccination of pregnant women with COVID-19 vaccine can accelerate the process of eliminating SARS-CoV-2 virus, and is considered safe for newborns. The recommended vaccination includes three doses.